Activities for road transport enterprises on indicators of workers and rolling stock productivity planning - L. S. Trofimova; A. P. Zhigadlo (Вестник СибАДИ)
Introduction. The emphasis is placed on modern requirements in the development of transport industry by improving the planning of the activities of road transport enterprises in terms of indicators that determine the productivity of workers and rolling stock, which are a function of the demand for transportation. The results of the activities of road transport enterprises depend on the labour productivity of each employee performing a specific function for the implementation of a specific contract and making a profit.Materials and methods. Planning is carried out using the conceptual provisions of the current planning of the work of a trucking company, taking into account the relationship of activities and the demand for transportation, methods of probability theory and mathematical statistics, scientific principles of education and training of workers for the transport industry.Results. The application of a new approach to planning is to combine the productivity of workers and the production of rolling stock of the Motor Transport Enterprises (MTE). This made it possible to develop a mathematical model and methodology, which takes into account that the productivity of workers must ensure the receipt of the planned income for each contract and its value will be planned within the confidence limits. When planning, probabilistic events are taken into account that occur during the development of sectors of the economy of the Russian Federation and affect the need for skilled staff. Mathematical modeling is carried out in relation to the real operating conditions of cargo transportation and specific functions of employees. The number of rolling stock and the required number of employees are determined by the development of rolling stock, by the development of a specific production function by an employee in modern conditions of contractual relations.Discussion and conclusions. The results of the study are intended for the practice of road transport enterprises at the stage of determining indicators of labor productivity of workers and rolling stock.